THE INFLUENCE OF HUMAN RESOURCE COMPETENCE AND THE USE OF INFORMATION TECHNOLOGY ON THE QUALITY OF BUMDes FINANCIAL STATEMENT IN KAMPAR REGENCY - Agustina, Ulviana; Marlina, Evi; Gita Suci, Rama (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study aims to analyze the effect of human resource competence and the use of information technology on the quality of financial statements of BUMDes in Kampar Regency. This quantitative research used primary data collected through a Likert scale questionnaire with a sample of 107 respondents, determined using simple random sampling and the Slovin formula. The data were analyzed using multiple linear regression with SPSS 26. The results show that both partially and simultaneously, human resource competence and the use of information technology significantly affect the quality of BUMDes financial statements in Kampar Regency.